Determination of secondary transitions and thermodynamic interaction parameters of poly (ether imide) by inverse gas chromatography - Çakar, F; Cankurtaran, O (SPRINGER, 2005)
The retention diagrams of poly( ether imide) for ethyl benzene, n-propyl benzene, isopropyl benzene, chloro benzene, n-butyl acetate, tert-butyl acetate, isoamyl acetate, n-nonane, n-decane, n-undecane, n-dodecane and n-tridecane were obtained by inverse gas chromatography technique. In this work, the slope changes on the diagram were assigned as secondary transitions. The secondary transition temperatures obtained by inverse gas chromatography technique are in good agreement with the ones obtained by thermally stimulated depolarization current in the literature. Specific retention volume, V-g, the weight fraction activity coefficients of the solvents at infinite solution, Omega(infinity)(1), Flory-Huggins polymer-solvent interaction parameters, chi(infinity)(12), equation-of-state polymer-solvent interaction parameters, chi(infinity)(12), effective exchange energy parameters, X-eff were determined. Later, the partial molar heat of sorption, Delta(H) over bar (1,sorp) and the partial molar heat of mixing, Delta(H) under bar (infinity)(1) were obtained. The solubility parameter of poly(ether imide), delta(2) was determined as 10.7 (cal/cm(3))(1/2) by extrapolation of the delta(2) values obtained by considering the free volume effects from studied temperature range to room temperature.
Keywords: STATISTICAL THERMODYNAMICS; ULTEM; EQUATION; STATE; Polymer Science